Fun English Games for ESP Students (Best Practices) - Wulandari, Eka; Mandasari, Yuyun Putri (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
Games are always heard to be fun, exciting, and adventurous to students. Everyone likes playing games, including fun English games for the students of the Nursing Department at Poltekkes Kemenkes Malang. This study explored the best practices of fun English games as an innovative pedagogical approach to enhance vocabulary acquisition among nursing students in higher education. The significance of this study lies in addressing the evolving landscape of nursing education and the need for dynamic teaching strategies aligned with the preferences of the digital-native generation, as emphasized by Prensky. The rationale for incorporating fun English games is grounded in principles of experiential learning and gamification, aligning with the ideas of scholars that playing games while learning English was very effective and efficient in improving vocabulary. This study reported that using games to learn English vocabulary is very useful and meaningful to the students. They showed a positive attitude towards the use of games in the classroom. Anticipated positive outcomes hold implications for nursing educators, curriculum developers, and policymakers, offering evidence-based recommendations to bridge the gap between theoretical insights and practical applications in nursing education.